Pengaruh Ekspor Dan Impor Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2014-2023 - Ria Wahyuni; Saarah Olinda Putri; Soni Aldi; Muhammad Kurniawan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research explains the influence of exports and imports on growth, stating that imports have a negative and insignificant effect on economic growth, while exports have a positive but significant effect on economic growth. According to the data that has been processed, it is stated that the results of the probability of exports and imports on economic growth in 2014- 2023.